Resin composition for outer layer of antibacterial article, molded article, and antibacterial article
By using the embedded segments containing the fatty polyether in the resin composition, the existing antibacterial materials are resolved in the lack of molding and coloring of the existing antibacterial materials, and achieved efficient antibacterial effects and excellent molding processability.
Patent Information
- Application Number
- CN202380047300.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-08
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-24
AI Technical Summary
The existing antibacterial materials have shortcomings in molding processability and color properties, and are prone to problems such as metal compounds exudation and degradation of toughness.
The embedded parts containing the aliphed polyether are used as a resin composition to achieve efficient antibacterial effects through its own antibacterial characteristics without adding metal compounds.
It achieves high antibacterial properties without bleeding of metal compounds, loss of toughness, or loss of color, and has excellent molding processability.
Smart Images

Figure BDA0005189174380000081 
Figure BDA0005189174380000091
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition for an outer layer of an antimicrobial article, a molded article, and an antimicrobial article. Background Art
[0002] As the infection of the new coronavirus spreads, society is increasingly concerned about hygiene, cleanliness, and health. For example, the demand for antibacterial properties is increasing in all living spaces in daily life, such as wallpaper, furniture, water supply materials in homes, equipment in places where food is manufactured and packaged in the food industry, walls, ceilings, floors, equipment used in toilets and kitchens in hospitals, parts and materials of equipment used in warm / humid conditions such as air conditioners and humidifiers, clothing, and general household items.
[0003] As such a material having antibacterial properties, for example, a material obtained by dispersing a metal compound composed of titanium oxide, cerium oxide, etc. in a resin is reported as in Patent Document 1. However, there is a problem that the metal compound seeps out to the surface of the product. In addition, there is a problem that the toughness of the mixed resin is reduced by the metal compound. In addition, there is a problem that it is difficult to produce a dark color.
[0004] On the other hand, as in Patent Document 2, polyvinyl alcohol having an amino group is reported as a polymer compound that exhibits antibacterial properties without adding an antibacterial agent.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 8-208414
[0008] Patent Document 2: International Publication No. 2017 / 171066 Summary of the invention
[0009] Problems to be solved by the invention
[0010] However, polyvinyl alcohol having an amino group, which is a polymer compound of Patent Document 2, has problems in terms of molding processability, and it is considered that a new material is needed.
[0011] The present invention aims to provide a resin composition for the outer layer of an antibacterial article which can exhibit high antibacterial properties by itself even without adding an antibacterial agent such as a metal compound, and can be processed as a molded body into an injection molded product, an extruded molded product, a film, a fiber, a nonwoven fabric and a foam.
[0012] Means for solving problems
[0013] The present inventors have found that a block copolymer containing an aliphatic polyether has high antimicrobial properties even without adding additives such as metal compounds, and that a resin composition containing the block copolymer exhibits antimicrobial properties.
[0014] That is, the present invention is as follows.
[0015] (1) A resin composition for an outer layer of an antimicrobial article, characterized in that it contains a block copolymer having an antimicrobial activity value of 2 or more after 24 hours, wherein the block copolymer is a block copolymer containing an aliphatic polyether.
[0016] (2) The resin composition for an antimicrobial article outer layer according to (1), wherein the block copolymer containing an aliphatic polyether is a thermoplastic polyester elastomer.
[0017] (3) The resin composition for an antimicrobial article outer layer according to (1) or (2), wherein the copolymerization ratio of the aliphatic polyether in the block copolymer containing the aliphatic polyether is 9% or more.
[0018] (4) The resin composition for an antimicrobial article outer layer according to (1) or (2), wherein the aliphatic polyether is an ethylene oxide adduct of poly(tetramethylene oxide) glycol or poly(propylene oxide) glycol.
[0019] (5) A molded article obtained by processing the resin composition for an outer layer of an antimicrobial article according to (1) or (2).
[0020] (6) An antimicrobial article, comprising: an outer layer of the antimicrobial article outer layer resin composition as described in (1) or (2).
[0021] Effects of the Invention
[0022] According to the present invention, a resin composition for an outer layer of an antimicrobial article is obtained which does not cause bleeding of metal compounds, reduction in toughness and coloration due to metal compounds, can exhibit high antimicrobial properties, and has excellent molding processability. DETAILED DESCRIPTION
[0023] Hereinafter, the present invention will be described in detail.
[0024] The resin composition for the outer layer of an antimicrobial article of the present invention contains a block copolymer having an antimicrobial activity value of 2 or more after 24 hours. The antimicrobial activity value of the block copolymer of the present invention after 24 hours in the antimicrobial test described later is 2 or more. The resin composition for the outer layer of an antimicrobial article of the present invention has antimicrobial properties by containing a block copolymer having an antimicrobial activity value of 2 or more after 24 hours.
[0025] In the present invention, "antibacterial property" refers to the property of inhibiting the growth of bacteria. The antibacterial property is evaluated by the antibacterial activity value (R) after 24 hours and the reduction rate (%) of the number of viable bacteria after 24 hours as described below.
[0026] The block copolymer of the present invention is a block copolymer containing an aliphatic polyether. The block copolymer containing an aliphatic polyether can inhibit the proliferation of bacteria by containing an aliphatic polyether. In addition, the block copolymer containing an aliphatic polyether has excellent molding processability.
[0027] [Aliphatic polyether]
[0028] As specific examples of aliphatic polyethers, poly(ethylene oxide) glycol, poly(propylene oxide) glycol, poly(trimethylene oxide) glycol, poly(tetramethylene oxide) glycol, poly(hexamethylene oxide) glycol, poly(nonamethylene oxide) glycol, copolymers of ethylene oxide and 1,2-propylene oxide, copolymers of tetrahydrofuran and oxepane, copolymers of tetrahydrofuran and oxepane, ethylene oxide adducts of poly(propylene oxide) glycol, and copolymers of ethylene oxide and tetrahydrofuran, etc. can be cited. Among them, ethylene oxide adducts of poly(tetramethylene oxide) glycol and / or poly(propylene oxide) glycol, and / or copolymers of ethylene oxide and tetrahydrofuran are preferably included. Among them, ethylene oxide adducts of poly(tetramethylene oxide) glycol and poly(propylene oxide) glycol are preferably included. Ethylene oxide adducts of poly(tetramethylene oxide) glycol and poly(propylene oxide) glycol are preferably included. In addition, for example, the poly(propylene oxide) glycol is poly-1,2-propylene oxide or polypropylene glycol, and the poly(tetramethylene oxide) glycol is poly(tetramethylene oxide) or polytetramethylene ether glycol.
[0029] The number average molecular weight of these aliphatic polyethers in a copolymerized state is preferably 300 to 6000. The number average molecular weight can be measured by general organic analysis.
[0030] The copolymerization ratio of the aliphatic polyether in the block copolymer containing an aliphatic polyether is more preferably 9% or more, more preferably 20% or more, more preferably 25% or more, more preferably 30% or more, more preferably 35% or more, more preferably 40% or more, more preferably 45% or more, more preferably 50% or more.
[0031] In addition, the copolymerization ratio of the aliphatic polyether of the block copolymer containing aliphatic polyether is the ratio of the aliphatic polyether unit as the diol component of the block copolymer containing aliphatic polyether. That is, the ratio of the amount of the water molecules generated by the ester bond generated from the aliphatic polyether of the raw material to the amount of the block copolymer containing aliphatic polyether as a whole is expressed in mass %. If the composition of the raw material is known, it can be directly calculated and obtained. In addition, the block copolymer containing aliphatic polyether can be obtained by structural analysis using NMR.
[0032] Examples of the block copolymer containing an aliphatic polyether of the present invention include thermoplastic polyester elastomers, thermoplastic polyamide elastomers, and thermoplastic polyurethane elastomers. Among them, thermoplastic polyester elastomers and thermoplastic polyamide elastomers are preferred, and thermoplastic polyester elastomers are more preferred.
[0033] [Thermoplastic polyester elastomer]
[0034] The thermoplastic polyester elastomer used in the present invention is a copolymer of a high melting point crystalline polymer segment and a low melting point polymer segment.
[0035] The high melting point crystalline polymer segment is a polyester formed from an aromatic dicarboxylic acid or an ester-forming derivative thereof, and a diol or an ester-forming derivative thereof.
[0036] Specific examples of the aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, phthalic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-2,7-dicarboxylic acid, anthracene dicarboxylic acid, diphenyl-4,4'-dicarboxylic acid, diphenoxyethane dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 5-sulfoisophthalic acid, and sodium 3-sulfoisophthalate. In the present invention, the aromatic dicarboxylic acids are mainly used, but a part of the aromatic dicarboxylic acids may be replaced by alicyclic dicarboxylic acids such as 1,4-cyclohexane dicarboxylic acid, cyclopentane dicarboxylic acid, and 4,4'-dicyclohexyl dicarboxylic acid, adipic acid, succinic acid, oxalic acid, sebacic acid, dodecanedioic acid, and aliphatic dicarboxylic acids such as dimer acid. Furthermore, ester-forming derivatives of dicarboxylic acids such as lower alkyl esters, aryl esters, carbonates, and acyl halides may also be used in the same manner.
[0037] In the present invention, two or more of the above acid components may be used, for example, a combination of terephthalic acid and isophthalic acid, terephthalic acid and dodecanedioic acid, terephthalic acid and dimer acid, and the like.
[0038] Next, as specific examples of the diol in the high melting point crystalline polymer segment, preferably, a diol having a molecular weight of 400 or less, for example, aliphatic diols such as 1,4-butanediol, ethylene glycol, 1,3-propylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, and 1,10-decanediol, alicyclic diols such as 1,1-cyclohexanedimethanol, 1,4-dicyclohexanedimethanol, and tricyclodecanediol, and benzyl alcohol, bis(p-hydroxy) Aromatic diols such as biphenyl, bis(p-hydroxy)diphenylpropane, 2,2'-bis[4-(2-hydroxyethoxy)phenyl]propane, bis[4-(2-hydroxyethoxy)phenyl]sulfone, 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 4,4'-dihydroxy-p-terphenyl, and 4,4'-dihydroxy-p-quaterphenyl may be used in the form of ester-forming derivatives such as acetylated forms, alkali metal salts, etc. These dicarboxylic acids, derivatives thereof, diol components, and derivatives thereof may be used in combination of two or more.
[0039] The low melting point polymer segment is an aliphatic polyether, but an aliphatic polyester or an aliphatic polycarbonate can also be used in combination. Specific examples of aliphatic polyesters include poly(ε-caprolactone), polyheptanolactone, polyoctalactone, polybutylene adipate, and the like. The aliphatic polycarbonate is preferably mainly composed of an aliphatic diol residue having 2 to 12 carbon atoms. Examples of these aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 2,2-dimethyl-1,3-propylene glycol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,9-nonanediol, and 2-methyl-1,8-octanediol.
[0040] The block copolymer containing aliphatic polyether of the present invention may contain additives such as antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, surfactants, lubricants, dyes, pigments, plasticizers, flame retardants, etc. as necessary within a range not impairing the purpose.
[0041] The antibacterial article outer layer resin composition of the present invention is characterized by having high antibacterial properties even without an antibacterial agent, so it is preferred not to include an antibacterial agent, or the antibacterial agent is less than 1% by mass, but it may also include an antibacterial agent. As the antibacterial agent, titanium oxide, zirconium oxide, aluminum oxide, manganese oxide, zinc oxide, tungsten oxide, cerium oxide, tin oxide, vanadium oxide, ruthenium oxide, yttrium oxide, chromium oxide, cobalt oxide, molybdenum oxide, silver oxide, copper iodide, cuprous oxide, barium titanate, potassium titanate, sodium titanate, strontium titanate, calcium titanate, magnesium titanate, lithium titanate, beryllium titanate, ammonium phosphomolybdate, silver ions, copper ions or zinc ions supported on quaternary ammonium salt compounds, silicates or phosphorus. Inorganic antibacterial agents obtained by inorganic compounds such as salts, thiabendazole, benzothiazole, 2-methylcarbonylaminobenzimidazole, biosol, thymol, 2,4,5,6-tetrachloroisophthalimide, VINYZENE (Mycocyanin, Biozin), quinoline copper, organic antibacterial agents obtained by supporting silver ions, copper ions or zinc ions on amino acids, deacetylated chitosan, amino acid saccharide compounds, cypress phenol or natural minerals, etc.
[0042] In addition, the antimicrobial article outer layer resin composition of the present invention can be composed only of the block copolymer comprising aliphatic polyether of the present invention, and can also add reinforcing materials such as other polymers, additives, talc, mica, glass flakes, calcium carbonate, clay, barium sulfate, glass beads, glass fiber, carbon fiber, cellulose nanofibers as required in the scope of not damaging the purpose. The antimicrobial article outer layer resin composition of the present invention preferably comprises 50~100 mass % of the block copolymer comprising aliphatic polyether of the present invention, more preferably comprises 80~100 mass %, and further preferably comprises 90~100 mass %.
[0043] Specific examples of the bacteria of the present invention include Helicobacter pylori, Mycobacterium tuberculosis, Staphylococcus aureus, Staphylococcus epidermidis, Group A Streptococcus, Group B Streptococcus, Mycobacterium leprae, Clostridium tetani, Bacillus anthracis, Neisseria meningitidis, Haemophilus influenzae, Vibrio cholerae, Yersinia pestis, Bordetella pertussis, Mycoplasma, Moraxella catarrhalis, Legionella pneumophila, Escherichia coli, Enterohemorrhagic Escherichia coli O157, Salmonella typhi, Salmonella typhimurium, Shigella bacteria, Campylobacter bacteria, Clostridium perfringens, Listeria, Bacillus cereus, Clostridium botulinum, Shigella-like Pseudomonas, Treponema pallidum, Neisseria gonorrhoeae, Chlamydia trachomatis, Actinomyces ilei, Streptococcus mutans, Citrobacter, Enterobacter, Serratia, Pseudomonas aeruginosa, Francisella tularensis, Streptobacillus moniliformis, and Bartonella henselae.
[0044] The molded article of the present invention is obtained by processing the resin composition for the outer layer of an antimicrobial article of the present invention. Specific forms of the molded article of the present invention include injection molded articles, extrusion molded articles, films, fibers, nonwoven fabrics, and foams.
[0045] The antimicrobial article outer layer resin composition of the present invention is preferably used for the outer layer of the article to which antimicrobial properties are to be imparted. That is, it is preferably a method for providing an article with antimicrobial properties, the method comprising a step of providing an outer layer of the article, the outer layer comprising the antimicrobial article outer layer resin composition of the present invention. The so-called outer layer here is the surface layer portion of a molded body formed by overlapping more than two layers, or the exposed surface of a single-layer molded body, for example, a film layer of an in-mold molded body, a contact layer of a two-color molded product, an exposed surface of an uncoated mask, etc.
[0046] Furthermore, the antimicrobial resin composition of the present invention is preferably used on the outer layer of an article in order to impart antimicrobial properties to the surface of the article.
[0047] Examples of uses of the antimicrobial article outer layer resin composition of the present invention include wallpaper, floor materials, curtains, clothing, trash cans, food packaging materials, adhesive plasters, masks, bandages, tableware, furniture, toys, bathroom components, toilet components, kitchen components, home appliances, filters (air purifiers), bedding (blankets, quilts, sheets), seats (car seats, train seats, aircraft seats, household chair seats), hanging handles, armrests, sponges (for cleaning, tableware washing, filter materials), diapers, cleaning tools, pollution spread prevention materials, automotive interior materials, etc.
[0048] Example
[0049] The effects of the present invention are described below by way of examples. In addition, the so-called % and part in the examples are all based on mass unless otherwise specified. The viable count using "E" in the table is an exponential expression (E expression) in which the decimal part is displayed before "E" and the exponential part is displayed after "E". In addition, the physical properties shown in the examples were measured as follows.
[0050] [Thermoplastic polyester elastomer (A-1)]
[0051] 270.0 parts of terephthalic acid, 234.0 parts of 1,4-butanediol, 0.1 parts of tetrabutyl titanate, and 0.1 parts of mono-n-butyl-monohydroxytin oxide were added to an esterification tank with a distillation tower and a stirrer, and the esterification reaction was started at 160°C and under a reduced pressure of 700 mmHg. Then, while slowly heating up, 59.0 parts of 1,4-butanediol were further added continuously. A transparent reaction product was obtained 3 hours and 40 minutes after the start of the reaction, and the reaction was terminated. After the esterification reaction was completed, 1.8 parts of tetrabutyl titanate as a polycondensation catalyst and 1.0 parts of "IRGANOX" 1330 (manufactured by BASF) as a stabilizer were added to the esterification tank. On the other hand, 686.0 parts of poly(tetramethylene oxide) glycol with a number average molecular weight of 1400 were added to the polycondensation tank, and the above-mentioned esterification reaction product was transferred from the esterification tank to the polycondensation tank. Furthermore, while stirring and polymerizing the reaction system in the polycondensation tank, the pressure was slowly changed from normal pressure to a high vacuum degree below 1 mmHg over 1 hour to a reduced pressure system, and at the same time the temperature was raised to 245°C. Polycondensation was carried out at 245°C and below 1 mmHg for 3 hours and 30 minutes to obtain a thermoplastic polyester elastomer (A-1) with a copolymerization ratio of aliphatic polyether components of 68%.
[0052] [Thermoplastic polyester elastomer (A-2)]
[0053] 312 parts of dimethyl terephthalate and 91 parts of dimethyl isophthalate, which will become high melting point crystalline polymer segments composed of crystalline aromatic polyester, 537 parts of ethylene oxide adduct of poly(propylene oxide) glycol with a number average molecular weight of 2150, which will become low melting point polymer segments composed of aliphatic polyether units, 167 parts of 1,4-butanediol, and 4 parts of titanium tetrabutoxide were added to a reaction vessel equipped with a ribbon-type stirring blade, and heated at 190-225°C for 3 hours to distill methanol out of the system. After adding 2 parts each of "IRGANOX" 1098 and 1019 (produced by BASF), the temperature was raised to 243°C, and then the pressure in the system was reduced to 0.2 mmHg over 50 minutes. Under this condition, polymerization was carried out for 3 hours to obtain a thermoplastic polyester elastomer (A-2) with a copolymerization ratio of 55% of the aliphatic polyether component.
[0054] [Thermoplastic polyester elastomer (A-3)]
[0055] 340.0 parts of terephthalic acid, 100 parts of isophthalic acid, 296.0 parts of 1,4-butanediol, 0.3 parts of tetrabutyl titanate, and 0.1 parts of mono-n-butyl-monohydroxytin oxide were added to an esterification tank with a distillation tower and a stirrer, and the esterification reaction was started at 160°C and a reduced pressure of 500 mmHg. Then, while slowly heating up, 74.0 parts of 1,4-butanediol were further added continuously. A transparent reaction product was obtained 3 hours and 40 minutes after the start of the reaction, and the reaction was terminated. After the esterification reaction was completed, 1.5 parts of tetrabutyl titanate as a polycondensation catalyst and 0.5 parts of "IRGANOX" 1098 (manufactured by BASF) as a stabilizer were added to the esterification tank. On the other hand, 495.0 parts of polybutylene glycol with a number average molecular weight of 1400 were added to the polycondensation tank, and the esterification reaction product was transferred from the esterification tank to the polycondensation tank. Furthermore, while stirring and polymerizing the reaction system in the polycondensation tank, the pressure was slowly changed from normal pressure to a high vacuum degree below 1 mmHg over 1 hour to a reduced pressure system, and at the same time the temperature was raised to 245°C. Polycondensation was carried out at 245°C and below 1 mmHg for 3 hours and 30 minutes to obtain a thermoplastic polyester elastomer (A-3) with a copolymerization ratio of aliphatic polyether components of 47%.
[0056] [Thermoplastic polyester elastomer (A-4)]
[0057] 501.0 parts of terephthalic acid, 326.0 parts of 1,4-butanediol, 0.3 parts of tetrabutyl titanate, and 0.2 parts of mono-n-butyl-monohydroxytin oxide were added to an esterification tank having a distillation tower and a stirrer, and the esterification reaction was started at 160°C and a reduced pressure of 650 mmHg. Then, while slowly raising the temperature, 81.0 parts of 1,4-butanediol were further continuously added, while the reduced pressure was changed to 500 mmHg from the middle of the reaction. A transparent reaction product was obtained 3 hours and 40 minutes after the start of the reaction, and the reaction was terminated. After the esterification reaction was completed, 2.0 parts of tetrabutyl titanate as a polycondensation catalyst and 0.5 parts of "IRGANOX" 1098 (manufactured by BASF) as a stabilizer were added to the esterification tank. On the other hand, 354.0 parts of polytetramethylene glycol having a number average molecular weight of 1400 was added to the polycondensation tank. The esterification reaction product was then transferred from the esterification tank to the polycondensation tank. Further, while the reaction system in the polycondensation tank was subjected to stirring polymerization, the pressure was gradually changed from normal pressure to a high vacuum degree of 1 mmHg or less over 1 hour to a reduced pressure system. At the same time, the temperature was raised to 245°C. Polycondensation was carried out at 245°C and 1 mmHg or less for 3 hours and 30 minutes to obtain a thermoplastic polyester elastomer (A-4) having a copolymerization ratio of 35% of an aliphatic polyether component.
[0058] [Thermoplastic polyester elastomer (A-5)]
[0059] 700.0 parts of terephthalic acid, 759.0 parts of 1,4-butanediol, 0.3 parts of tetrabutyl titanate, and 0.1 parts of mono-n-butyl-monohydroxytin oxide were added to an esterification tank with a distillation tower and a stirrer, and the esterification reaction was started at 160°C and a reduced pressure of 500 mmHg. A transparent reaction product was obtained 3 hours and 40 minutes after the start of the reaction, and the reaction was terminated. After the esterification reaction was completed, 1.5 parts of tetrabutyl titanate as a polycondensation catalyst and 0.5 parts of "IRGANOX" 1330 (manufactured by BASF) as a stabilizer were added to the esterification tank. On the other hand, 80.0 parts of polybutylene glycol with a number average molecular weight of 1000 were added to the polycondensation tank, and the esterification reaction product was transferred from the esterification tank to the polycondensation tank. Furthermore, while stirring and polymerizing the reaction system in the polycondensation tank, the pressure was slowly converted into a reduced pressure system from normal pressure to a high vacuum degree below 1 mmHg over 1 hour, and at the same time the temperature was raised to 245°C. Polycondensation was carried out at 245°C and below 1 mmHg for 3 hours and 30 minutes to obtain a thermoplastic polyester elastomer (A-5) with a copolymerization ratio of 8% of the aliphatic polyether component.
[0060] [PBT resin (B)]
[0061] トレコン TM 1100S (manufactured by Toray Industries, Inc.). A polymer of terephthalic acid and 1,4-butanediol.
[0062] [Test piece molding]
[0063] The pellets were injection molded using an injection molding machine NEX-1000 manufactured by Nissei Plastic Industry Co., Ltd. to obtain a square plate-shaped test piece of 80×80×2 mm. Since injection molding is possible, the pellets can be processed into injection molded products, extrusion molded products, films, fibers, nonwoven fabrics, and foams.
[0064] [Antibacterial test]
[0065] The antimicrobial activity was measured basically in accordance with JIS Z 2801:2012 Antimicrobial activity test for antimicrobial treated products.
[0066] Escherichia coli and Staphylococcus aureus were used as bacteria. 100 μl of a predetermined bacterial solution was dripped onto a test piece cut into 5 cm squares, and a covering film (4 cm squares) was placed from above to evenly spread the bacterial solution. After standing at 35 degrees for 24 hours, 10 ml of a cleaning solution was added, and the bacteria were washed with SCDLP medium by aspiration. The pour plate culture method was used to determine the number of viable bacteria in the cleaning solution by the number of colonies in the agar medium (CFU / cm 2 The detection limit of viable bacteria count is 0.63 (CFU / cm 2 ).
[0067] [Antibacterial activity value and viable bacteria count reduction rate]
[0068] Regarding the antibacterial activity value (R) after 24 hours and the viable bacterial count reduction rate (%) after 24 hours, the viable bacterial count immediately after inoculation (0 hours) was set as U0, and the viable bacterial count after 24 hours was set as U 24 , was obtained by the following formula.
[0069] Antibacterial activity value after 24 hours (R) = lg10(U0)-lg10(U 24 )
[0070] Reduction rate of viable bacteria after 24 hours (%) = [(U0-U 24 )×100] / U 0。
[0071] [Examples 1 and 2]
[0072] Evaluation was carried out using the above-mentioned thermoplastic polyester elastomer (A-1).
[0073] [Examples 3 and 4]
[0074] Evaluation was carried out using the above-mentioned thermoplastic polyester elastomer (A-2).
[0075] [Examples 5 and 6]
[0076] Evaluation was carried out using the above-mentioned thermoplastic polyester elastomer (A-3).
[0077] [Examples 7 and 8]
[0078] Evaluation was carried out using the above-mentioned thermoplastic polyester elastomer (A-4).
[0079] [Comparative Examples 1 and 2]
[0080] Evaluation was performed using the above-mentioned PBT resin (B).
[0081] [Comparative Examples 3 and 4]
[0082] Evaluation was carried out using the above-mentioned thermoplastic polyester elastomer (A-5).
[0083] Table 1 shows the materials of Examples and Comparative Examples, the ratio of the aliphatic polyether component, the number of viable bacteria at 0 hour and 24 hours, the antibacterial activity value after 24 hours, and the reduction rate of the number of viable bacteria after 24 hours.
[0084] From Examples 1 to 8, it is understood that the thermoplastic polyester elastomers (A-1), (A-2), (A-3), and (A-4) containing an aliphatic polyether component have a large effect of reducing the number of viable cells.
[0085] Furthermore, it can be seen from Comparative Examples 1 to 4 that in the PBT resin (B) and the thermoplastic polyester elastomer (A-5) not containing an aliphatic polyether component, the number of viable bacteria after 24 hours was greater than the number of viable bacteria at 0 hours, and since the antibacterial activity value was less than 2, there was no reduction effect. Since Comparative Examples 1 to 3 had no reduction effect, the antibacterial activity value after 24 hours and the reduction rate of the number of viable bacteria after 24 hours were 0.
[0086]
[0087] Table 2
[0088]
Claims
1. A resin composition for an outer layer of an antibacterial article, characterized in that: The present invention contains a block copolymer having an antimicrobial activity value of 2 or more after 24 hours, wherein the block copolymer is a block copolymer containing an aliphatic polyether.
2. The antimicrobial article outer layer resin composition according to claim 1, characterized in that: The block copolymer containing aliphatic polyether is a thermoplastic polyester elastomer.
3. The resin composition for an outer layer of an antimicrobial article according to claim 1 or 2, characterized in that: The copolymerization ratio of the aliphatic polyether in the block copolymer containing an aliphatic polyether is 9% or more.
4. The resin composition for an outer layer of an antimicrobial article according to claim 1 or 2, characterized in that: The aliphatic polyether is an ethylene oxide adduct of poly(tetramethylene oxide) glycol or poly(propylene oxide) glycol.
5. A molded body obtained by processing the resin composition for an outer layer of an antimicrobial article according to claim 1 or 2.
6. An antimicrobial article, comprising an outer layer of which the antimicrobial article outer layer resin composition according to claim 1 or 2 is used.
Citation Information
Patent Citations
Resin composition and antimicrobial and antifungal methods
JP1996208414A
Antibacterial and antiviral composition
WO2017171066A1